OVO acceptability and its innovative characteristics - Venna Kintan (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2022)
OVO is a financial application that was launched widely in September 2017. Since its launch, OVO has successfully received ten million users in July 2018. This study aims to investigate innovative characteristics that determine its rapid acceptability. Roger's (1983) diffusion of innovation theory underlines the study. The data were collected from 150 respondents who have used the OVO application at least once in the last six months, chosen judgmentally. This study found that OVO acceptability is determined by relative advantage and observability. Compatibility does not affect OVO acceptance. In addition, complexity influences OVO acceptability negatively. The four determinants can explain 72% of OVO acceptability. The researcher recommends that companies conduct counseling, seminars, and even workshops on OVO applications so that more people can better know OVO. This research still focuses on people below 31 years old. Further research can focus on older. Original Article | Turnitin